Peran Guru Dalam Mengembangkan Minat Literasi Di Sd Negeri 21 Usaha Jaya - Salam, Abd.; Gurium, Muhammad Riski; Ikhsan, Muh. (LPPM IAIN Sorong, 2022)
This study aims to analyze the role of teachers in developing literacy interest in Sekolah SD Negeri 21 Usaha Jaya. This research uses descriptive qualitative method with case study approach. Data collection techniques are carried out by Interviews, Observations, and Documentation of principals, teachers, and students. The result of this study is to analyze the role of teachers in developing students' literacy interests, including the strategies and approaches used. It will provide a deep understanding of the role of teachers in developing and enhancing efforts in developing students' literacy interests in SD Negeri 21 Usaha Jaya. According to the results of the study, it can be reviewed that 1) literacy activities play a role in increasing students' interest in reading, 2) obstacles in carrying out literacy activities in schools include the lack of infrastructure, the role of parents, the methods applied are less varied and low discipline of students in the process of habituating literacy activities, and 3) the efforts made by the school in overcoming these obstacles are by providing socialization about literacy activities, adding facilities and holding tutoring activities as a means of active participation of students.